2019
DOI: 10.1177/1833358319887743
|View full text |Cite
|
Sign up to set email alerts
|

Data quality in healthcare: A report of practical experience with the Canadian Primary Care Sentinel Surveillance Network data

Abstract: Data quality (DQ) is the degree to which a given dataset meets a user’s requirements. In the primary healthcare setting, poor quality data can lead to poor patient care, negatively affect the validity and reproducibility of research results and limit the value that such data may have for public health surveillance. To extract reliable and useful information from a large quantity of data and to make more effective and informed decisions, data should be as clean and free of errors as possible. Moreover, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…Epidemiology studies and surveillance programs have shown the potential of using administrative health data to identify cases with chronic diseases in Canada [ 2 4 , 8 , 13 , 30 34 ] and many other countries [ 35 44 ]. A few studies have also linked administrative health data to large population-based cohorts, to carry out disease surveillance beyond the primary self-report data possible for these cohorts [ 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology studies and surveillance programs have shown the potential of using administrative health data to identify cases with chronic diseases in Canada [ 2 4 , 8 , 13 , 30 34 ] and many other countries [ 35 44 ]. A few studies have also linked administrative health data to large population-based cohorts, to carry out disease surveillance beyond the primary self-report data possible for these cohorts [ 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second issue raised by Wynants et al has to do with data impact, viz. the need, in diagnostic, prognostic, and policy-level prediction models, for complete, consistent, accurately measured, relevant, and timely data that is of sufficient quantity to produce reliable out-of-sample generalization (Ehsani-Moghaddam, 2019;Hienrich et al, 2007;Wang et al, 1995). Wynants et al highlight the fact that the studies that they appraise face the common hazard that small sample sizes (drawn from scarce and geographically limited patient populations) will lead to overfitting and compromised generalizability (Foster et al, 2014;Riley 3 The problem here was that the designers of the model chose health care costs as the measurable proxy for the target concept of ill health.…”
Section: Pitfalls Of Covid-19-related Research Ii: Adverse Data Impactmentioning
confidence: 99%
“…Data quality can also pose a challenge if there is no way to assess quality of individual datasets that are distributed. For many real-world problems, data can be inherently poor-quality due to uncertainty, subjectivity, errors, or subjected to adversarial attack 11 – 13 . This problem is exaggerated when private data at each locality cannot be manually seen or verified.…”
Section: Introductionmentioning
confidence: 99%